Motivasi Pemanfaatan Ruang Publik Terpadu Ramah Anak (RPTRA) Bagi Anak-Anak Dalam Mengisi Waktu Luang - Farhan Nur Sya’ban; Moh. Amin Tohari (Journal of Creative Student Research, 2024)
Limited green open space makes children play in inappropriate places, such as roads. This problem arises due to development that does not prioritize children's rights. Many children cannot enjoy their childhood because of limited public spaces. For example, there are no adequate play facilities available, an unhealthy environment, or public spaces that are not child-friendly. RPTRA exists in order to provide child-friendly integrated public spaces equipped with physical facilities, functioning as a means of providing services and activities, especially for children and residents. This research aims to determine the motivation for using public space for children in Child-Friendly Integrated Public Spaces (RPTRA). This research uses survey research with a quantitative approach. Using questionnaire methods. The sample of respondents was 30 children. The technique for determining informants uses purposive sampling data. Based on the results of this research, public spaces motivate children to play because the facilities provided and the security and comfort provided by the RPTRA itself make children visit the RPTRA. The intensity of children visiting RPTRAs is considered quite high because almost every child often visits RPTRAs. The data results show that more children visit the RPTRA because they do sports activities such as playing ball, playing in the playground area and jogging. Then other factors such as wanting to play in the park, because they are bored at home, comfort and safety are the top reasons for children to visit RPTRA.